Chapter Esercizi di pedagogia critica. In omaggio a Paolo Federighi e alla "Scuola fiorentina" - Colazzo, Salvatore (Studies on Adult Learning and Education, 2022)
The essay seeks to emphasize how post-World War II Italian pedagogy was renewed by opening it up to considering the educational potential of social contexts, thereby managing to connect with the most vital currents in the international debate, which were interested in deepening the school/society nexus. It grasps in Vico an extraordinary precursor of themes explored and clarified in recent times. With this choice it wants to indicate the existence of a carsic current in national reflection of great importance, to be studied, deepened and claimed in order to escape the risks of foreignness that so many of today's pedagogical studies manifest. He points out in the research of the so-called "School of Florence" the design of some very fruitful trajectories in the field of social and community pedagogy, grasping in this its specific contribution to the renewal of Italian pedagogy.